REKAYASA SOSIAL UNTUK MENGATASI DEPENDANT MENTALITY MASYARAKAT TERHADAP BANTUAN PEMERINTAH DI DESA BONTOMINASA KECAMATAN BULUKUMPA KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This research is motivated by the government's efforts in alleviating poverty using Government Assistance which fosters a dependent mentality. The main problem in this study is the exposure of social engineering to overcome the mindset of depending on the community for government assistance to become an independent mentality in Bontominasa Village, Bulukumpa District, Bulukumba Regency. This type of research is included in qualitative study using a research approach, namely a sociological approach. Furthermore, the data sources used are primary data and secondary data. For data collection through observation, interviews, and documentation. Then the data processing and analysis techniques were carried out through three stages, data reduction, data presentation (data display), and drawing conclusions. The results of the research show that 1) Some social engineering that can be done in overcoming the mentality of depending on the community for government assistance is changing the paradigm of people's thinking about the nature of assistance and increasing community capacity (capacity building) through motivational training, job training, and reviving the entrepreneurial spirit. 2) Before receiving government assistance, it is necessary to go through several stages first. 3) Government assistance as a solution in poverty alleviation not only has a positive impact on the community but also has a negative impact.